2022
DOI: 10.3389/fpsyt.2022.804491
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Efficacy and Experiences With Narrative Exposure Therapy in Severe Mentally Ill Patients With Comorbid Post-traumatic Stress Disorder Receiving Flexible Assertive Community Treatment: A Mixed Methods Study

Abstract: BackgroundPatients with severe mental illness with repeated interpersonal trauma and post-traumatic stress disorder (PTSD) have a negative illness progression. Traumas are often not treated because of their vulnerability. Narrative exposure therapy (NET) is an effective trauma therapy. It is unknown whether NET is effective and tolerable in these patients receiving community mental healthcare.ObjectivesThe objectives of this study are (1) to gain insights into patients’ experiences before, during, and after NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…There were N = 33 studies that met inclusion criteria presented in Table 1 [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Publication years ranged from 2003–2023.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were N = 33 studies that met inclusion criteria presented in Table 1 [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Publication years ranged from 2003–2023.…”
Section: Resultsmentioning
confidence: 99%
“…There were three studies that analyzed Acceptance and Commitment Therapy (ACT) [ 32 , 37 , 39 ] and one with compassionate imagery [ 43 ]. Several additional studies involved a form of trauma therapy, including one study each of eye movement desensitization and reprocessing EMDR [ 41 ], trauma-focused imaginal exposure [ 42 ], prolonged exposure [ 47 ], narrative exposure therapy [ 55 ], and two studies including trauma-integrated psychotherapy for psychosis (TRIPP) [ 61 , 62 ]. In addition, two studies analyzed a technology-enhanced/assisted psychotherapy: Slowmo [ 45 ] and virtual reality therapy for negative symptoms [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many interventions included either a specific trauma-focused therapy (n = 7), such as Eye Movement Desensitization and Reprocessing (EMDR), or a trauma-focused therapy in combination with another intervention (n = 14), including within an intensive trauma program (n = 4). Studies with a single, specific trauma-focused therapy included EMDR (n = 4), [86][87][88]91 Narrative Exposure Therapy (NET) (n = 2), 89,90 Prolonged Exposure (PE) (n = 1), 91 and Hypnotherapeutic Olfactory Conditioning (HOC) (n = 1); 85 all but a group-based bilateral stimulation intervention reported dissociation improvement. This study enrolled participants with severe dissociative symptoms from a specialty trauma and dissociation clinic.…”
Section: Trauma-focused Psychotherapiesmentioning
confidence: 99%
“…This study enrolled participants with severe dissociative symptoms from a specialty trauma and dissociation clinic. 88 Other populations studied included PTSD or trauma exposure (n = 5), [85][86][87]89,91 including those with comorbid BPD 90 and severe mental illness with repeated interpersonal trauma. 89 Treatments that combined a trauma-focused modality with another therapy were also common (n = 14 studies); all but two reported improvements in dissociation.…”
Section: Trauma-focused Psychotherapiesmentioning
confidence: 99%